Control strategies for seamless transfer between the grid-connected and islanded modes of a microgrid system - V. Lavanya; N. Senthil Kumar (International Journal of Electrical and Computer Engineering (IJECE), 2020)
Design of control strategies for Distributed generation systems is very important to achieve smoother transition between the grid connected and islanding modes of operation. The transition between these two modes of operation should be seamless, without any severe transients during the changeover. In this paper, two different control strategies namely inverter output current control and indirect grid current control for the seamless transfer between the modes of operation has been explored for the suitability. The design and analysis of the cascaded control loops based on Proportional Integral (PI) controller has been dealt in detail for both inverter output current control and indirect grid current control strategy. Control parameters are designed using the control system toolbox in MATLAB. A 10kW grid connected microgrid system has been designed and simulated in MATLAB/Simulink and the results are presented under grid connected operation, islanding operation and the transition between the modes considering fault condition in the grid side. The simulation studies are carried out using both the control strategies and the results are presented to validate the design methodology.